Insecticidal properties of several essential oils on the house fly (Musca domestica L.) - Pavela, Roman (Phytotherapy research, 2008)
The insecticidal activity of 34 essential oils, extracted from plants, was screened against the house fly, Musca domestica L. under laboratory conditions. Essential oils from Pogostemon cablin proved to be the most efficient at a lethal dose of 3 microg/fly after topical application. Eight oils (P. roseum, O. vulgare, O. compactum, M. pulegium, O. basilicum, O. majorana, T. vulgaris and P. graveolens) were lethal in doses ranging from 10 to 20 microg (10, 13, 13, 13, 15, 17, 18 and 19 microg/fly, respectively). The lethal doses of another 13 oils were ascertained in the range 20-50 microg/fly, nine oils had lethal doses of 50-100 microg. For two oils, the lethal dose could not be for the topical application. In the fumigant test, the most efficient proved to be Mentha pulegium oil (4.7 microg/cm(2)). For 10 oils, a lethal dose between 5 and 10 microg/cm(2) was ascertained (T. bipinata, C. aurantifolia, T. occidentalis, T. matschiana, S. officinalis, T. vulgaris, M. quinquenervia, O. compactum, C. limonum and R. officinalis, respectively). For the other 10 oils a lethal dose from 10 but to 80 microg/cm(2) was ascertained, and for 13 oils the lethal dose was higher than the highest dose in the tests.
Keywords: Araceae; Geraniaceae; testy toxicity; Rutaceae; Houseflies; Insecticides; Myrtaceae; borovicovité; Animals; zvířata; Oils, Volatile; moucha domácí; hluchavkovité; oleje prchavé; insekticidy; Lamiaceae; Plant Oils; Toxicity Tests; oleje rostlin; Pinaceae